A FORMAÇÃO E O CONHECIMENTO DO PROFESSOR DE EDUCAÇÃO ESPECIAL - Camizão, Amanda Costa (2021)
This research objectivated to evaluate the advances, limits and potentialities of the necessary knowledge regarding the teacher education who works in Special Education and its locus which has been presented throughout the history of teachers’ education in Brazil, in academic production area, in teacher training policies and in municipal hiring notices. For this we took as a basis the historical-cultural and critical theory which are based on the historical-dialectical materialism and which allowed us to analyze and understand issues that are specific to the area of education and Special Education. To achieve this objective we consider the history of Special Education, documents concerning the training of teachers in the area, scientific production about teachers’ education in the Special Education area, and municipal notices for hiring Special Education teachers and their interpretations on the documents about terminology, attributions, knowledge and requirements for the requested position. Our results show that there is no policy for teachers’ education on Special Education that can systematize the proposal and ensure ethical-political commitment to the area. This can be understood as a way of not breaking with previous trends leaded in Special Education. This fact provides opportunities for the participation of specialized institutions with the direct influence of the medical-psychological model, the restricted educational training for students with disabilities and the consequent limited social participation. Special Education lacks systematization of the knowledge that constitutes it. Although cite superficially about cultural-historical theory, the municipalities begin to attempt theoretical appropriation on learning and development process and the knowledge about defectology, but when they appear it is always in a fragmented way and most of the time wrong. We defend the thesis that the essential knowledge to the Special Education teacher's praxis, aimed at ensuring the appropriation of culture and the humanization process of students called the target audience of Special Education, will depend on a training policy that brings together general and specific and an ethical-political commitment based on consolidated theoretical-methodological bases for this purpose and that dialogue with the policies of valorization of this professor and with the processes of his professionalization.